Panduan Pelaksanaan Pemeriksaan Radiografi Kedokteran Gigi Pada Pasien Anak - Intan Farizka; Dhara Nandary; Delly Wijaya (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: Dental radiographic examinations are diagnostic tool in oral and dental treatment, including in children. The use of radiation exposure in children is such a challenge for dental practicioners, either about the radiation safety or the patient management. Good quality radiograph should be obtained with minimal radiation and in condition of pediatric patients that sometimes are uncooperative. Literature review: Children have increased risk of disease than adults since their cells are more sensitive to radiation. Therefore dental radiography examinations in children should be performed according recommended steps as following: select radiographic technique for individual’s needs not for routine, choose the fastest image receptor, always use tyroid collar, collimate beam to area of interest, minimize exposure factors. Type of radiographic should be selected as indications. E-speed film, F-speed film, and digital sensor can reduce radiation dose. Tyroid collar and collimator are used for protect healthy tissue. Exposure factors should be minimized by decreasing exposure time. Several modification techniques may be needed to handle unique character of pediatric patients. Communication with “tell, show, do” technique should be undergone to manage patients. Modified radiographic techniques may be helpful to gain patient cooperation, such as Lollipop radiographic technique as desensitization technique, reverse bitewing technique, extraoral periapical technique, panoramic radiography for patient who refused intraoral film and last choice is anestethic. Reverse bitewing technique and extraoral periapical technique can be used to handle gagging reflex. Conclusion: The important issues of radiographic examination in children are about radiation safety and patients management to obtain good quality radiographs. Radiographic examination must have advantages greater than risk of radiation exposure in children. “Tell, show, do” communication technique and radiographic technique modification are part of management principle of children to gain patient cooperation.